Diagnostic Significance of Intraoperative Ultrasound Contrast in Evaluating the Resection Degree of Brain Glioma By Transmission Electron Microscopic Examination - Yu, Shu-Qing; Wang, Ji-Sheng; Chen, Si-Yuan; Liu, Xiang-Ming; Li, Yan; Ding, Yi-Ming; Li, Xiao-Ya; Sun, Yi-Lin; Chen, Hui (Chinese medical journal, 2015)
Background：Contrast-enhanced ultrasound is a dynamic and continuous modality providing real-time view of vascularization and flow distribution patterns of different organs and tumors.In order to evaluate the diagnostic significance of intraoperative contrast-enhanced ultrasound in assessing the resection degree of brain glioma by transmission electron microscopic （TEM） examination,it is important to have specific knowledge about contrast-enhanced ultrasound.Methods：Ultrasound contrast was applied in operations of 120 cases of brain glioma,to evaluate the degree of tumor resection.Biopsy tissues were obtained the suspicious residual tumors surrounding the tumor cavity.The sensitivity and specificity of the residual tumors were determined by the intraoperative ultrasound contrast according to TEM examination results.Results：There were 44 cases of low-grade gliomas and 76 cases of high-grade gliomas.Three hundred and sixty biopsy tissues were obtained.The sensitivity of intraoperative ultrasound contrast in diagnosing the residual tumor was 62.2%,while the specificity degree of it was 92.8%.The consistency coefficient of the ultrasound contrast diagnosis and TEM examination results was 0.584 （Kappa =0.584）,which was between 0.4 and 0.6,therefore it was of medium consistency.Conclusions：Intraoperative ultrasound contrast was of a high sensitivity and specificity in evaluating the excision degree of tumor.The consistency of the residual tumor rate detected,respectively,by ultrasound contrast and TEM examination was of medium consistency.The application of intraoperative ultrasound contrast can improve the resection rate of brain glioma.